KEGAGALAN PEMBENTUKAN POLONG DAN BUI PADA BAUHINIA TOMENTOSA L. (FABACEAE) - IMAMUDDIN, HARTATI (Research Center for Biology-Indonesian Institute of Sciences, 1987)
H. IMAMUDDIN. 1987.The failure of pods and seeds development of Bauhinia tomentosa L. Suppl. Berita Biologi 3 : 35 - 37.Microscopic,observation to study the failure of pods and seeds development of Bauhinia tomentosa L. was conducted.Several buds,6 - 21 mm long, were diserved with paraffin method.The results showed that the failure of pods and seeds development of B. tomentosa were not caused by either flower morphology, pollen fertility or nticrospore development,but by abnormal development of saccus embrionalis,followed by incomplete development of egg cell,which made the flowers aborted before receptive.